2020
DOI: 10.3758/s13428-020-01377-5
|View full text |Cite
|
Sign up to set email alerts
|

Spanish affective normative data for 1,406 words rated by children and adolescents (SANDchild)

Abstract: Most research on the relationship between emotion and language in children relies on the use of words whose affective properties have been assessed by adults. To overcome this limitation, in the current study we introduce SANDchild, the Spanish affective database for children. This dataset reports ratings in the valence and the arousal dimensions for a large corpus of 1406 Spanish words rated by a large sample of 1276 children and adolescents from four different age groups (7, 9, 11 and 13 years old). We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…The available evidence suggested that young children's ratings of valence were more extreme than those of adolescents and adults (Monnier and Syssau, 2017;Vesker et al, 2018). Furthermore, youngest children considered more words to be positive than adolescents (Sabater et al, 2020). These findings have confirmed that the affective evaluations of information vary with age.…”
Section: Age-related Differences In Emotional Functionsmentioning
confidence: 74%
See 3 more Smart Citations
“…The available evidence suggested that young children's ratings of valence were more extreme than those of adolescents and adults (Monnier and Syssau, 2017;Vesker et al, 2018). Furthermore, youngest children considered more words to be positive than adolescents (Sabater et al, 2020). These findings have confirmed that the affective evaluations of information vary with age.…”
Section: Age-related Differences In Emotional Functionsmentioning
confidence: 74%
“…In addition to language differences, affective meanings of words seem to vary with age. Age-related differences in emotional context have been evidenced when words were rated by children and adults (Monnier and Syssau, 2017;Vesker et al, 2018Vesker et al, , 2020Morningstar et al, 2019;Sabater et al, 2020). The available evidence suggested that young children's ratings of valence were more extreme than those of adolescents and adults (Monnier and Syssau, 2017;Vesker et al, 2018).…”
Section: Age-related Differences In Emotional Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Different univariate neural network models were trained to predict the emotional valence (output of neural networks) from amodal LSA vector representations (input of neural networks) only in the child developmental stage. In this case, neural networks were trained and validated predicting the child's emotional judgments of the SANDchild data set (Sabater, Guasch, Ferré, Fraga, & Hinojosa, 2020) using the vector Note: Neural network models that were trained and validated in the child semantic space were also tested in the adult semantic space representations of the child semantic space. As it will be described below, not all the words in the child semantic space took part in the training and validation set of the neural network as we only used words from the SANDchild data set (908 words for training and 302 words for validation data sets).…”
Section: Methodsmentioning
confidence: 99%